An Algorithm Research of Ground-Space Integrated Scheduling TT&C Resources of Orbit Determination of GNSS Constellation - Zhang Tianjiao; Li Jing; Li Zexi; Xiang Ming (2013 Fourth International Conference on Intelligent Systems Design and Engineering Applications, 2013)
Space-based TT&C technology is an effective way to solve the problem of resources dissatisfaction of ground-based TT&C system. Based on the research of multi-satellites TT&C resources scheduling problem, this article proposes a normalized description for all types of resources which suitable for scheduling algorithm design; For the orbit determination tasks of satellites of GNSS `Beidou II', this article analyzes the constraints of this particular TT&C mode, and takes weighted TT&C time of satellite orbit determination tasks as target to establish space-ground integrated TT&C network scheduling model, then designs a scheduling algorithm based on concurrent ACO(ant colony algorithm). Simulation results show that, this scheduling strategy can effectively improve the determination tasks allocation efficiency, thus reducing the dependence of ground-based TT&C network.